Combustion characteristics of briquettes produced from three binders and torrefied gmelina arborea (robx.) sawdust (2023)
Considering the energy potential of briquettes, there are several undesired harmful qualities such as intense yellow flame and smoke. Torrefaction was deemed a suitable technological solution, therefore, the study investigated the combustion properties of briquettes made from Gmelina arborea sawdust and three binders used print paper (UPP), newsprint (Np) and clay (CL). Materials and Methods: Experiments were conducted using a hydraulic press and a biomass stove. The 3 torrefied feedstock samples (TS 30, TS 45 and TS 60 min) were mixed with binders at 10, 20, 30, 40 and 50% w/w at 1.67 kPa applied pressure and 5 min residence period to produce briquettes. The results were statistically analyzed at significance level using ANOVA. Results: Briquette densities decreased with an increase in torrefaction time with strong positive correlations between densities of the same binder type, concentration and torrefaction time. An increase in binder concentration enhanced the combustion characteristics of UPP and Np briquettes positively, with significant negative effects on CL briquettes. Torrefied used printing paper briquette burns with non-luminous flame and reduced smokiness as binder concentration increases, while newsprints briquette produced excessive smokes. Briquettes produced from used printing papers at 45 min torrefaction had better performances in terms of energy values, product flammability and reduced smokiness. Clay-bonded briquettes had delayed ignition 7-10 min and failed to burn with flame, rather than by char combustion. Conclusion: Torrefaction time, binder type and concentration had significant positive effects on the combustion characteristics. Clay had poor effects on combustion characteristics.